PENGEMBANGAN MODEL PEMBELAJARAN SANTIAJI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - AHDAR, AHDAR; BUHAERAH, BUHAERAH; BUHAERAH, BUHAERAH (Kuriositas: Media Komunikasi Sosial dan Keagamaan, 2014)
The problems that need to be solved through this research is âhow the process and outcomes of learning model development briefng to develop critical thinking skills that meet the criteria of a valid, practical and effective ??â Presentation of verbal and cognitive strategy training into a combination of cognitive strategies in learning to develop skills critical thinking. So this research is directed to develop a model of learning that provide instructions or guidance on verbal cognitive strategies are accompanied by cognitive strategy training in identifying and justifying the concept, menggenralisasi, analyzing algorithms, and problem solving with the title learning model development briefng (MPS). The results achieved in the trials I and II trials, namely: (1) general MPS has practical, but there are aspects of the model components fraction implemented, (2) MPS has not been effective, the results of the frst trial demonstrated the ability of teachers to manage MPS category of âgoodâ while in the second trial demonstrated the ability of teachers to manage learning in the category of âvery goodâ, and the studentsâ response to the positive MPS learning, while other indicators have not berpenuhi is expected MPS student activity and critical thinking skills have not been met. Results achieved III trials, namely: (1) generally meets the criteria MPS practical, diamana MPS components in the category largely accomplished even some of them are implemented in full, (2) effective MPS (student activities all within a time limit of tolerance, ability teachers manage learning in the excellent category, the response has been positive studentsâ learning, and critical thinking skills are minimal in the high category has been reached.